Visualization of Pitch in Slendro and Diatonic Scales - Parung, Christabel; Saidi, Acep Iwan; Sunarya, Yan Yan; Sihombing, Riama Maslan (LP2M ISBI Bandung, 2025)
This study investigates the visual representation of pitch in two musical scales: the diatonic scale and the Javanese Slendro scale. This research shows how scales are perceived and depicted visually by engaging five young adults in a free-drawing study. Using Jakobson’s intersemiotic translation for analysis, participants were provided with sound stimuli first and asked to draw their visualization of scales using lines, form, and color. The results revealed that the diatonic scale was consistently represented with structured and sequential visuals, indicating familiarity and linearity. On the other hand, Slendro was visualised with more significant variability and fluidity. This study shows that the visual representation of the musical element of pitch does not stand alone but is also influenced by the musical scale and the listener’s familiarity with it.